2022
DOI: 10.1039/d2tc01119k
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence coupled to electric and magnetic surface lattice resonance in periodic arrays of zirconia nanoparticles

Abstract: Zirconia is transparent from near-ultraviolet through the entire visible region, and here we utilize the periodic arrays of zirconia nanoparticle to excite electric and magnetic SLRs in the visible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We also observed the out-coupling enhancement by the nanoparticle array along the (−1, 0) SLR mode that appears as a sharp and dispersive line starting from λ = 650 nm at θ = 10°and red-shifts as θ increases. The emission out-coupling by SLR 40,41 and the separated evaluation of in-and out-coupling had been discussed in previous publications. 51 A horizontal band of "emission" was also detected at 580 nm, which is the exact wavelength of the incident beam and the excited SLR.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed the out-coupling enhancement by the nanoparticle array along the (−1, 0) SLR mode that appears as a sharp and dispersive line starting from λ = 650 nm at θ = 10°and red-shifts as θ increases. The emission out-coupling by SLR 40,41 and the separated evaluation of in-and out-coupling had been discussed in previous publications. 51 A horizontal band of "emission" was also detected at 580 nm, which is the exact wavelength of the incident beam and the excited SLR.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Previous works have shown that SLR is capable of significantly enhancing the light–matter interaction of fluorescent dye molecules and can enhance both the in-coupling efficiency and the directional out-coupling of the fluorescent emission. The enhancement in the in-coupling efficiency is due to the confinement of the EM field in the vicinity of the nanoparticle array, and hence, the localized and enhanced field strength would induce a stronger absorption by the fluorescent molecules. , On the other hand, the angle-dependent fluorescence enhancement is enabled by first enhancing the emission rate of the fluorescent molecules through the increased local density of state near the nanoparticle array, also known as the Purcell effect, and then, the enhanced emission is radiatively out-coupled to specific angles through diffraction with the nanoparticle array. …”
Section: Introductionmentioning
confidence: 99%
“…[4] [5] Many dielectrics such as Si and TiO 2 are also absorptive in the UV due to their direct bandgap smaller than the UV energy. [6] The transparent and high refractive index material, such ZrO 2 [7] and HfO 2 [8] is required in the UV region.…”
Section: Introductionmentioning
confidence: 99%